IMPACTS OF SEPARATION BETWEEN INDIA AND PAKISTAN IN VIC SARIN’S PARTITION MOVIE (2007): A SOCIOLOGICAL APPROACH - HIDAYAT, I. FARID (2011)
This study is aimed to show the impacts of separation between India and Pakistan in Vic Sarin’s Partition movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. This research is qualitative research; type of data of the study is text and image taken from two data sources; primary and secondary. The primary data source is the Partition movie directed by Vic Sarin and released in 2007. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both of the data are collected through library research and analyzed by using descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound and editing are related to each other. Sociological analysis shows a close relationship between the movie production and the social reality underlying it, such as the impacts between India and Pakistan separation.